1995
DOI: 10.1021/j100044a031
|View full text |Cite
|
Sign up to set email alerts
|

Photon-induced reactions of aromatics adsorbed on rough and smooth silver surfaces

Abstract: We have investigated the thermal and photon-induced chemistry of several aromatics adsorbed on smooth and roughened Ag( 11 1) surfaces at low temperatures (1 10 K). Pyrazine, pyridine, 3-chloropyridine, and chlorobenzene quantitatively desorb from Ag( 11 1) near 200 K. After roughening the surface with 2 kV Ar ion bombardment, the breadth of the molecular desorption curves increases, and there is a high-temperature tail due to desorption from defect sites produced by the roughening process. Upon UV photolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Interesting photochemical effects of NPs do not only derive from their increased surface/volume ratio, but also from their unique optical, electronic, and catalytic properties which can be tuned by size, shape, and/or support material. Plasmon-induced enhancement of the photoreactivity of adsorbates via field enhancement on roughened metal surfaces 10,11 and on MNPs (Refs. [7][8][9] Nevertheless, the number of experimental investigations that address the effects of size and/or plasmon excitation on the photochemistry of adsorbates on MNP surfaces is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Interesting photochemical effects of NPs do not only derive from their increased surface/volume ratio, but also from their unique optical, electronic, and catalytic properties which can be tuned by size, shape, and/or support material. Plasmon-induced enhancement of the photoreactivity of adsorbates via field enhancement on roughened metal surfaces 10,11 and on MNPs (Refs. [7][8][9] Nevertheless, the number of experimental investigations that address the effects of size and/or plasmon excitation on the photochemistry of adsorbates on MNP surfaces is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Following the characterisation of the mechanism of adsorbate photochemistry on metal surfaces, there has been increasing interest in enhancing or controlling its rate. Strategies proposed have included modification of the substrate morphology to promote photochemistry at defect sites [18] or through excitation of particle plasmon resonances [19][20][21][22][23]. Indeed a number of plasmon enhanced substrate excited processes have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…An ion sputter gun ͑Phi Model 04-161͒, operating at a beam energy of 2.0 kV, with the beam defocused, produced a beam current at the crystal of 5 A cm Ϫ2 , as measured by a picoammeter ͑Keithley͒. Although the electron microscope employed in the present experiments lacked the resolution required to see these nanometer scale features, the conditions used are identical to these earlier studies, 7,9 and it is assumed that the present surface had a similar morphology. This was confirmed by separate measurements of the beam profile using a 2 mm diam platinum Faraday cup mounted on a translation stage.…”
Section: Methodsmentioning
confidence: 90%
“…15 The roughened surface was prepared following exactly the procedure described by Goncher et al 7 The Ag͑111͒ crystal was argon ion sputtered at room temperature for 90 min by backfilling the UHV chamber with argon ͑Messer Grieshiem, Ͼ99.999% purity͒ to a pressure of 3ϫ10 Ϫ5 Torr. 9 This revealed features of around 75 nm as well as smaller ͑tens of nm͒ features, superimposed upon the larger bumps. Analysis of the damage induced by the beam on a silicon target confirmed that the Ar ϩ beam profile was uniform over the dimensions of the Ag͑111͒ crystal.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation